Television - Swinson Arthur (Wheaton Of Exeter, 1964)
How it Began, How a Programme is Made, The Job of the Writer, The Job of the Director, The Job of the Actor, Film in Television, Spotting the Programme, Appreciating Television, The Future of Television, Index.